PENGARUH DIAMETER PIRINGAN DAN ELASTISITAS KARET PENGUPAS TERHADAP KINERJA ALAT PENGUPAS LADA TIPE PIRINGAN - HIDAYAT, TATANG; RISFAHERI, RISFAHERI (Pusat Penelitian dan Pengembangan Perkebunan, 2001)
To produce while pepper using traditional method, the ripe berries are soaked in a river or a pond for 10-14 days prior to decorticating. To improve the traditional method. Research Institute for Spice and Medicinal Crops has designed pepper decorticator to support the white pepper processing. This decorticator has a good function, hut its performance still need to be improved, as it still produces high percentage of white pepper damage. This experiment was aimed to at improving (he performance of the pepper decorticator. The experiment was conducted from July to Ocktobcr 1999 and divided into two steps i.e. preliminary and main experiment. The treatments applied on Ihe main experiment were (I) disc diameter (18, 20, and 22 cm) and (2) rubber elasticity (5.34, 7.74, 9.79, and 15.02 N/mm). The experiment was designed as a completely randomized, arranged factorially in three replications. The pepper variety used for the experiment was Lampung Daun Lebar. The disc distance of pepper decorticator in this experiment was set at 3.5 cm based on the preliminary experiment. Results showed that the optimal disc diameter and nibber elasticity was 20 cm and 7.74 N/mm respectively. Decorticator performance on the optimal condition were : decorticated pepper 97.25%, white pepper damage as pepper defect 2.46% and as broken pepper 1.98% respectively and the capacity of decorticator was 42.27 kg/hours. In general, the quality of while pepper produced met the National Standard of Indonesia.